How does investment efficiency affect financial distress risk? Evidence from China - Geng, Huixia; Zhu, Hongbing; Lau, Wei Theng; Mohd Nor, Normaziah; Ab Razak, Nazrul Hisyam (Elsevier B.V., 2025)
Motivated by the high financial distress risk (Hereafter, FDR) level and extensively inefficient investment behaviors in China, this paper aims to explore the relationship between firms’ investment efficiency and FDR. Utilizing Chinese A-share market data spanning 2008–2020, we find that over-investment linearly exacerbates FDR, while under-investment has a U-shaped relationship with FDR. Detecting the underlying mechanisms, we find that over-investment exacerbates FDR through linearly declining firms’ cash holding and investing cash flow while increasing firms financing cash flow, and under-investment impacts FDR through the inverted U-shaped relationship with operating cash flow and U-shaped relationship with firms’ financing cash flow. Our findings hold up well after various robustness tests, providing new implications of firm life circle theory and static trade-off theory in the process of investment efficiency influencing FDR.